Human-sensor dialogue in participatory sensing - Paxton, Mark Christopher (2009)
Participatory sensing is an emerging field that uses pervasive technology to create new forms of sensing networks combining people, personal devices, and other sensors. Pervasive computing technology forms an essential component, used to report data and coordinate activities. This thesis reviews research in participatory sensing and key fields related to it: pervasive computing, observation networks and public engagement with science.